1981
DOI: 10.1007/bf01443939
|View full text |Cite
|
Sign up to set email alerts
|

The beta strength function and the astrophysical site of ther-process

Abstract: The beta strength function has been calculated for ~ 6 000 nuclei between the line of beta stability and the neutron drip line. The calculations -performed by using a schematical Brown-Bolsterli model -yield more reliable beta decay half lives, P, values and/?-delayed fission rates than the strongly oversimplified assumptions on S~ used up to now in astrophysical calculations. The calculated beta rates are shown in this paper to be decisive in the discussion of the problem of the astrophysical site of the r-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0
1

Year Published

1982
1982
1994
1994

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 45 publications
0
62
0
1
Order By: Relevance
“…While with the use of the -on the average -distinctly shorter T1/2 of [11] in an explosive He-burning scenario [29] considerable improvement over earlier attempts could be obtained as far as the reproduction of positions and relative heights of the r-abundance peaks at A ~ 130 and 195 are concerned [32], difficulties were met in the region around A=80 [12,33]. These calculations showed that, when starting from the Fe group seed nuclei, not even the N = 50 shell (corresponding to the A ~ 80 abundance peak) could be reached during the short duration of the neutron flux of a few tenths of a second in explosive He-burning, and solar-system r-abundances could not be re-produced anymore (see also [34]).…”
Section: Astrophysical Implicationsmentioning
confidence: 95%
See 2 more Smart Citations
“…While with the use of the -on the average -distinctly shorter T1/2 of [11] in an explosive He-burning scenario [29] considerable improvement over earlier attempts could be obtained as far as the reproduction of positions and relative heights of the r-abundance peaks at A ~ 130 and 195 are concerned [32], difficulties were met in the region around A=80 [12,33]. These calculations showed that, when starting from the Fe group seed nuclei, not even the N = 50 shell (corresponding to the A ~ 80 abundance peak) could be reached during the short duration of the neutron flux of a few tenths of a second in explosive He-burning, and solar-system r-abundances could not be re-produced anymore (see also [34]).…”
Section: Astrophysical Implicationsmentioning
confidence: 95%
“…These calculations showed that, when starting from the Fe group seed nuclei, not even the N = 50 shell (corresponding to the A ~ 80 abundance peak) could be reached during the short duration of the neutron flux of a few tenths of a second in explosive He-burning, and solar-system r-abundances could not be re-produced anymore (see also [34]). Therefore, to overcome this problem, the r-process calculations presented in [32] started from 7aNis0. As is discussed in [12], also the assumption of an (n, 7)-(% n) equilibrium in the attempt of [32] seems to be inconsistent with the adopted astrophysical model.…”
Section: Astrophysical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to achieve a homogeneous mixture of 233pa tracer and the uranium salt, 233pa solution in 6M HC1 was added to UO2(NO3)2.6H20 powder, stirred to give a wet mass, dried for one day at room temperature in vacuum, and finally milled to give the finely powdered material used as target for the neutron bombardments. Furthermore, in some cases we determined chemical yields via 7-ray activities of 6.7 h 234gPa present in the decay chain of 23sU with a branch of 0.13% [1][2][3][4][5][6][7][8][9][10][11][12]. Within the statistical accuracy the chemical yields determined via the artificially added 233pa tracer, and, alternatively determined via 234gPa, a natural decay product of 23SU, were the same.…”
Section: Chemical Yields For Protactiniummentioning
confidence: 99%
“…Therefore, in the energy interval 2.56-3.46 MeV one has to rely on theoretical calculations of S~. Microscopic calculations of S~ are available [1,2], however the predictive power of such calculations, in particular for deformed nuclei, is still unsatisfying [3]. For the purpose of a simple estimate of the order of magnitude of P~I we use the extremely gross approximation S~=const.…”
Section: F(zq-e) the Latter Being Approximated By (Q -E) S The Ft-mentioning
confidence: 99%